Mechanised Harvesting of Safflower (Carthamus tinctorius L., fam. Asteraceae) – a review - Muscalu, Adriana; Tudora, Cătălina; Sorica, Cristian; Anghelache, Dragoş (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Safflower (Carthamus tinctorius L., family Asteraceae) is part of the species with a “wide biodiversity portfolio”, which has genetic potential, but is underutilized for commercial cultivation. Such species offer viable agricultural alternatives in response to climate change, being adapted to cultivation on less fertile, even marginal, land. The cultivation potential of Safflower is high, but in our country there are few cultivated areas. The lack of documentation regarding the cultivation technology, as well as the lack on the market of biological material necessary for sowing the crops, led to the disinterest of the growers in this plant. However, in recent years, the attention given to this crop has increased, due to more and more intense lack of water and limitation of precipitation, which cause a huge deficit in the production of oilseeds, the Safflower being, however, resistant to these conditions. To these added are the consumers’ preference for the healthy oil, with less saturated fat, for which Safflower oil is well known. Also, the species has medicinal properties, and edible dyes are extracted from its flowers. Every part of the Safflower plant can be used after processing, as food, phytomedicine, biofuel, for ornamental purposes, etc. Collecting the petals is a difficult operation, especially for the thorny varieties of the species, and it is done manually. The high labour costs, as well as the difficulty of finding it, create problems for the development of the processing industry of this plant. The paper presents a brief summary of the technical systems for the mechanized harvesting of Safflower depending on its uses, including the current state of research regarding the design and experimentation of robots intended for the collection of inflorescences.